APPLICATION AFFECTIVE LEARNING STRATEGIES IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Ariny Maitasya Tanzila; Stevani Anjelia; Gusmaneli (Yayasan Zia Salsabila, 2025)
Affective learning strategies in Islamic Religious Education (PAI) play a crucial role in shaping the character, attitudes, and moral values of students as an important foundation in building a moral society. PAI learning not only emphasizes cognitive aspects, but also affective integration that directs students to have religious behavior in their daily lives. This study aims to analyze the urgency, implementation models, and implementation challenges of affective learning strategies in PAI based on literature studies from various recent studies. The results show that affective strategies such as teacher exemplary, value clarification, positive attitude habituation, and emotional reinforcement contribute significantly to students' character building. However, obstacles such as difficulties in attitude evaluation and limited learning time remain a challenge that needs to be overcome with a collaborative approach between teachers, students and the environment. The Qur'anic texts, especially Q.S. Al-Mujadilah verse 11, strengthen the foundation that value-based learning is part of increasing one's degree of faith and knowledge. Thus, the application of affective learning strategies that are integrated, systematic, and adaptive is an urgent need in improving the quality of PAI education in the modern era.